A Highly Cost‐Efficient Large‐Scale Uniform Laminar Plasma Jet Array Enhanced by V–I Characteristic Modulation in a Non‐Self‐Sustained Atmospheric Discharge. Issue 6 (9th January 2020) - Li, Jing; Wang, Jing; Lei, Bingying; Zhang, Tongyi; Tang, Jie; Wang, Yishan; Zhao, Wei; Duan, Yixiang
Abstract: Developing cost‐efficient large‐scale uniform plasma jets represents a significant challenge for high performance in material processing and plasma medicine. Here, a V – I characteristic modulation approach is proposed to reduce the discharge power and increase the plasma scale and chemical activity in non‐self‐sustained atmospheric direct‐current discharges. The electric field in discharge space is optimized to fundamentally empower simultaneously initiating all discharge cells far below Townsend breakdown potential and stably sustaining each plasma jet at low voltage. These strategies create a crucial step to fabricating a flexible and compact low‐power large‐scale uniform laminar plasma jet array (LPJA) with high activity in cheap argon. The mechanisms behind the discharge enhancement are revealed by combining V – I characteristic examination and a modulation model. Compared with conventional arrays, this LPJA possesses the widest size (90 mm) and raises its uniformity from 30% to 97%. Comparing different discharge modes shows that the LPJA scale is surprisingly increased nearly by 4 times with the discharge power reduced from 7.4 to 4.8 W. The methodology provides a highly cost‐efficient roadmap to break through the bottleneck of restricting low‐power discharge, large‐gap discharge, large‐scale discharge, parallel‐multi‐electrode discharge, and uniform discharge together. This advance will meet the urgent need for various plasma applications. Abstract : A V – I characteristic modulation approach is proposed in non‐self‐sustained direct‐current discharge to greatly reduce the discharge power and largely increase the plasma scale and chemical activity. In conjunction with the electric field optimization to realize the discharge simultaneity and stability, a highly cost‐efficient large‐scale uniform laminar plasma jet array is fabricated for material processing and plasma medicine.